Eficacia comparativa de acupuntura manual-electroacupuntura versus tratamiento farmacológico complejo B-Glucocorticoide en la parálisis de Bell - Báez Maldonado, José Antonio (Universidad Autónoma Metropolitana, 2007)
OBJECTIVE To compare the efficacy of acupuncture and electropunture versus pharmacological treatment vitamins/dexametasone in patients with Bell¶s facial palsy(PB). MATERIAL AND METHODS omparative, open, observational, prospective, and longitudinal study was done. Seventy patients of either sex attending to the acupunctural clinic of the Universidad Autónoma Metropolitana - Iztapalapa México D F with PB were enrolled. Patients were randomized allocated in either two groups A and B. Then each group was stratified in groups of age ranging from 18-30 years, 31-46 years, 46-60 years and <60 years. Group A received acupuncture if PB was present for < 10 days or electroacupunture for PB lasting >10 days in the following points of acupuncture: Stomach Meridian: (Dicang) 5 (Daying), and 6 (Jiache), Bladder Meridian: V 2 (Zanzhu), Gallbladder Meridian: VB 14 (Yangbai), VB 20 (Fengchi). Large Intestine Meridian: IG 4 (Hegu), IG 20 (Yingxiang), Small Intestine Meridian: SI 18 (Quanliao), SI 19 (Tinggong), Triple Energizer Meridian: SJ 17 (Yifeng), SJ 23 (Sizhukong), Conception vessel: Ren 24 (Chengjiang). After 10 days of PB VB 20 (Fengchi) was withdrawn, and then electropuntura was applied. Group ³%´ received 10 applications of vitamin B complex 500 mg and dexametasone 1 mg/kg/d IM. Diagnosis of Bell's paralysis was made by symptomatology and severity of the clinical picture by means of the system developed by House and Brackmann (HB), Scale of Gradation of the Muscular Facial Function of House-Brackmann, with 6 categories or grades of dysfunction. Grade I: normal function in all the territories. · Grade II: Slight dysfunction of the musculature, noticeable only with carefully inspection. At rest normal facial symmetry. · Grade III: moderate dysfunction. Clear difference between both sides without be disfiguring itself. Incompetence for complete closing eye; movement of frontal region present, asymmetry of the oral commissure in full movements. At rest normal symmetry and tone. · Grade the IV: dysfunction moderately severe. There was no movement of frontal region; inability to close totally the eye, facial spasm. · Grade V: severe dysfunction. Only slight perceptible motor activity. At rest asymmetry. · ·Grade VI: total paralysis. There is no facial movement. Total loss of the tone. Grades were registered at baseline and after 10 sessions treatment. RESULTS group (A) with a HB (face flaccidity) showed grade HB IV 11 patients, HB V, 19 patients, grade HB, 5 patients; after treatment, the average improve of HB were as described: grade of HB I 26 patients, grade of HB II, 5 patient, grade of HB III, 1 patients, grade of HB IV 2 patients. At baseline patients of the group (A) with a HB (difficulty to swallow foods and drinks) showed grade of HB IV 3 patients, grade of HB V 18 patients, grade of HB IV 14 patients at the beginning of the study; after treatment, the improve HB were as follows: grade of HB I 27 patients, grade HB II, 6 patients, grade HB IV, 1 patient. At baseline, group (A) with a HB (changes in the appearance of the face) showed grade of HB IV 3 patients, grade of HB V 17 patients, grade of HB VI 15 patients. After treatment the improve of HB were as follows grade of HB I 27 patients, grade of HB II 2 patients, grade of HB III 3 patients, grade of HB IV 1 patient, grade of HB V 1 patient. At baseline, group (A) with a HB (difficulty for the face expressions, to make faces) showed HB grade V 16 patients, grade VI 19 patients. After treatment, grade of HB were as follows grade I, 27 patients, grade HB II, 2 patients, grade III 2 patients, grade IV 2 patient grade V 1 patient. Of the group (A) with a HB (dribbling presented/displayed by incapacity in the control of face muscles) figures were as follows at baseline grade of HB VI 35 patients; after treatment grade HB I 28 patients, grade HB II 1 patient, grade HB III 2 patients, grade HB IV 1 patient, grade HB V 2 patients. Of the group (A) with a HB (dry eye secondary to the incapacity to close the affected eye lid). Figures were as follows: at baseline: HB V 14 patients, grade HB V 21 patients; after treatment: HB grade HB I 25 patients, grade HB II 4 patients, grade HB III 2 patients, grade HB IV 2 patients, grade HB V 1 patient. Of the group (B) with a HB (face flaccidity), at baseline: HB IV 10 patients, grade HB V 20 patients, grade HB VI 5 patients. After treatment: HB, grade HB I 23 patients, grade HB II 6 patient, grade HB III 1 patients, grade HB IV 1 patients, grade HB V 1 patients. Of the group (B) with a HB (difficulty to swallow foods and drinks), at baseline: grade HB IV 4 patients, grade HB V 14 patients, grade HB VI 17. After treatment: HB, grade HB I 23 patients, grade HB II 2 patients, grade HB III 4 patients, grade HB V 1 patient, grade HB VI 2 patients. Of the group (B) with a HB (changes in the facial appearance), at baseline grade HB IV 2 patients, grade HB V 13 patients, grade HB VI 20 patients. After treatment: grade HB I 23 patients, grade HB II 2 patients, grade HB III 4 patients, grade HB V 1 patient, grade HB VI 2 patients. Of the group (B) with a HB (difficulty for the face expressions, to gesticulate), at baseline grade HB V 23 patients, grade HB VI 12 patients. After treatment: grade HB I 23 patients, grade HB II 2 patients, grade HB III 4 patients, grade HB V 3 patients. Of the group (B) with a HB (dribbling presented/displayed by incapacity in the control of facial muscles), at baseline grade of HB VI 35 patients. After treatment: grade HB I 23 patients, grade HB II 2 patients, grade HB III 4 patients, grade HB IV 3 patients. Of the group (B) with a HB (dry eye secondary to the incapacity to close the affected eye lid), at baseline: grade HB V 12 patients, grade HB VI 23 patients. After treatment: grade HB I 23 patients, grade HB II 2 patients, grade HB III 2 patients, grade HB IV 2 patients, grade HB V 1 patient, grade HB VI 2 patients. CONCLUSIONS · We found no significant differences between groups in the levels of weakness of the facial muscles, and the levels of difficulty to swallow food. · The study of the changes in the appearance of the face, the grades of difficulty for the facial expressions/do grimaces), the grades of slavering for disability in the control of the muscles of the face, in the grades of grade of rareness of the eye, secondary to the disability to close the affected eyelid showed a significant favourable difference in the treatment of manual acupuncture and electropuntura versus conventional treatment with vitamins and corticosteroids.; OBJETIVOS. Comparar la eficacia del tratamiento de la acupuntura versus tratamiento farmacológico vitaminas-glucocorticoides en pacientes con parálisis facial Bell (PB). MATERIAL Y MÉTODOS. Estudio comparativo, abierto, observacional, prospectivo y longitudinal de una muestra de 70 pacientes que acudieron a la clínica de acupuntura de la Universidad Autónoma Metropolitana ± Iztapalapa México DF, por presentar parálisis facial de Bell. Los pacientes de cualquiera sexo fueron asignados de manera aleatoria a los grupos A y B, cada uno con 35 pacientes. Los pacientes de cada grupo fueron subdivididos en subgrupos de edades de 18-30 años, 31-45 años, 46-60 años y < de 60 años. Al grupo A se le aplicó acupuntura si tenía menos de 10 días de haber presentado la PB, o cumplidos 10 días con PB se les aplicó electropuntura en los siguientes puntos de acupuntura: Canal de Estómago: (Dicang), E 5 (Daying), E 6 (Jiache), Canal de Vejiga: V 2 (Zanzhu), Canal Vesícula Biliar: VB 14 (Yangbai), VB 20 (Fengchi). Canal Intestino Grueso: IG 4 (Hegu), IG 20 (Yingxiang), Canal Intestino Delgado: ID 18 (Quanliao), ID 19 (Tinggong), Canal San Jiao: SJ 17 (Yifeng), SJ 23 (Sizhukong), Canal Ren: Ren 24 (Chengjiang). Después de 10 días de haber aparecido la parálisis se suprimió el punto VB 20 (Fengchi), y se aplicó electropuntura. Al grupo B se le realizaron 10 aplicaciones de complejo vitamínico B 500 mg y dexametasona 1 mg/kg de peso corporal/día IM. Se realizó el diagnóstico de parálisis de Bell por sintomatología y gravedad del cuadro mismo mediante el sistema de calificación de House y Brackmann (HB), Escala de gradación de la función muscular facial de House - Brackmann, que establece 6 categorías o grados de disfunción: · Grado I: función normal en todos los territorios. · Grado II: disfunción leve. Ligera o leve debilidad de la musculatura, apreciable tan sólo en la inspección meticulosa. Simetría en reposo normal. Grado III: disfunción moderada. Diferencia clara entre ambos lados sin ser desfigurante. Incompetencia para el cierre palpebral completo; hay movimiento de región frontal, asimetría de la comisura bucal en movimientos máximos. Simetría y tono normal en reposo. · Grado IV: disfunción moderadamente grave. Debilidad y/o asimetría. Simetría y tono normal en reposo. Sin movimiento en la región frontal; imposibilidad para cerrar totalmente el ojo. Sincinesias. Espasmo facial. · Grado V: disfunción grave. Tan sólo ligera actividad motora perceptible. Asimetría en reposo. · Grado VI: parálisis total. No hay movimiento facial. Pérdida total del tono. Entonces se calcularon y compararon los grados que prevalecían al inicio y al final del tratamiento. RESULTADOS. Del grupo (A) con una escala HB de flacidez facial inicial: grado IV 11 pacientes; grado V 19 pacientes; grado VI 5 pacientes. Final: grado I 26 pacientes; grado II 5 pacientes; grado III 1 paciente; grado IV 2 pacientes. Del grupo (A) con una escala HB de dificultad para consumir alimentos y bebidas inicial: grado IV 3 pacientes; grado V 18 pacientes; grado VI 14 pacientes al principio del estudio. Final: grado I 27 pacientes; grado II 6 pacientes; grado IV 1 paciente. Del grupo (A) con un escala HB de cambios en la apariencia de la cara inicial: grado IV 3 pacientes; grado V 17 pacientes, grado VI 15 pacientes. Final: grado I 27 pacientes, grado II 2 pacientes, grado III 3 pacientes, grado IV 1 paciente, grado V 1 paciente. Del grupo (A) con una escala HB de dificultad para las expresiones faciales, hacer muecas, inicial: grado V 16 pacientes, grado VI 19 pacientes. Final: grado I 27 pacientes, grado II 2 pacientes, grado III 2 pacientes, grado IV 2 pacientes, grado V 1 paciente. Del grupo (A) con una escala HB de babeo presentado por incapacidad en el control de los músculos faciales inicial: grado VI 35 pacientes. Final: grado I 28 pacientes, grado II 1 paciente, grado III 2 pacientes, grado IV 1 paciente, grado V 2 pacientes. Del grupo (A) con una escala HB de resequedad del ojo secundario a la incapacidad de cerrar el parpado afectado convenientemente inicial: grado V 14 pacientes, grado VI 21 pacientes. Final: grado I 25 pacientes, grado II 4 pacientes, grado III 2 pacientes, grado IV 2 pacientes, grado V 1 paciente. Del grupo (B) con una escala HB de flacidez facial inicial: grado IV 10 pacientes, grado V 20 pacientes, grado VI 5 pacientes. Final: grado I 23 pacientes, grado II 6 paciente, grado III 1 pacientes, grado IV 1 paciente, grado V 1 paciente. Del grupo (B) con una escala HB de dificultad para consumir alimentos y bebidas inicial: grado IV 4 pacientes, grado V 14 pacientes, grado VI 17. Final: grado I 23 pacientes, grado II 2 pacientes, grado III 4 pacientes, grado V 1 paciente, grado VI 2 pacientes. Del grupo (B) con una escala HB de cambios en la apariencia de la cara inicial: grado IV 2 pacientes, grado V 13 pacientes, grado VI 20 pacientes. Final: grado I 23 pacientes, grado II 2 pacientes, grado III 4 pacientes, grado V 1 paciente, grado VI 2 pacientes. Del grupo (B) con una escala HB de dificultad para las expresiones faciales, hacer muecas inicial: grado V 23 pacientes, grado VI 12 pacientes. Final: grado I 23 pacientes, grado II 2 pacientes, grado III 4 pacientes, grado VI 3 pacientes. Del grupo (B) con una escala HB de babeo presentado por incapacidad en el control de los músculos faciales inicial: grado VI 35 pacientes. Final: grado I 23 pacientes, grado II 2 pacientes, grado III 4 pacientes, grado IV 3 pacientes. Del grupo (B) con una escala HB de resequedad del ojo secundario a la incapacidad de cerrar el parpado afectado inicial: grado V 12 pacientes, grado VI 23 pacientes. Final: grado I 23 pacientes, grado II 2 pacientes, grado III 2 pacientes, grado IV 2 pacientes, grado V 1 paciente, grado VI 2 pacientes. CONCLUSIONES. · Al final del estudio se encontró que los grados de flacidez de los músculos faciales, los grados de dificultad para consumir alimentos no presentaron diferencias significativas. · El estudio de los cambios en la apariencia de la cara, los grados de dificultad para las expresiones faciales /hacer muecas), los grados de babeo por incapacidad en el control de los músculos de la cara, en los grados de grado de resequedad del ojo secundaria a la incapacidad de cerrar el párpado afectado mostró una diferencia significativa favorable al tratamiento de acupuntura manual y electropuntura versus el tratamiento convencional con vitaminas y corticosteroides.